2022
DOI: 10.1111/azo.12436
|View full text |Cite
|
Sign up to set email alerts
|

Sex dimorphism and evidence of sexually selected traits: A case study on the killifish Aphaniops stoliczkanus (Day, 1872)

Abstract: Variability is a basic element of biology and is an essential component of evolutionary processes. Phenotypic variability within a species can be linked to ecological, environmental and ontogenetic factors, but also to sex-related differences (Martinez et al., 2019). The phenomenon of sex-related variability often appears in the form of sex dimorphism, which is usually manifested in differences in the size, colour or shape of morphological structures (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…The majority of fishes are gonochoristic and have various sexually dimorphic characteristics in their secondary sexual characteristics 30 . Distinguishing characteristics for the morphological qualities of many teleosts have been documented, including body color, ornamental patterns, breeding tubercles on the snout, pectoral fins and scales, fin hooks, body shape, fin size and shape [31][32][33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of fishes are gonochoristic and have various sexually dimorphic characteristics in their secondary sexual characteristics 30 . Distinguishing characteristics for the morphological qualities of many teleosts have been documented, including body color, ornamental patterns, breeding tubercles on the snout, pectoral fins and scales, fin hooks, body shape, fin size and shape [31][32][33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
“…Some aspects of observation that could be a basic source of information for knowledge of differences between males and females include morphometric characters, meristics, length-weight relationships, and condition factors to determine fish age. Research related to sexual dimorphism has been widely reported in freshwater and marine fish species (Timahakim et al, 2019;Putra et al, 2023;Garcia and Zuanon, 2019;Sukmaningrum et al, 2019;Abduh et al, 2020;Mainero et al, 2023).…”
Section: Introductionmentioning
confidence: 99%